Polymorphic and Higher-Order G-Quadruplexes as Possible Transcription Regulators: Novel Perspectives for Future Anticancer Therapeutic Applications - Rigo, Riccardo; Groaz, Elisabetta; Sissi, Claudia (Pharmaceuticals (Basel, Switzerland), 2022)
In the past two decades, significant efforts have been put into designing small molecules to target selected genomic sites where DNA conformational rearrangements control gene expression. G-rich sequences at oncogene promoters are considered good points of intervention since, under specific environmental conditions, they can fold into non-canonical tetrahelical structures known as G-quadruplexes. However, emerging evidence points to a frequent lack of correlation between small molecule targeting of G-quadruplexes at gene promoters and the expression of the associated protein, which hampers pharmaceutical applications. The wide genomic localization of G-quadruplexes along with their highly polymorphic behavior may account for this scenario, suggesting the need for more focused drug design strategies. Here, we will summarize the G4 structural features that can be considered to fulfill this goal. In particular, by comparing a telomeric sequence with the well-characterized G-rich domain of the KIT promoter, we will address how multiple secondary structures might cooperate to control genome architecture at a higher level. If this holds true, the link between drug-DNA complex formation and the associated cellular effects will need to be revisited.
Keywords: folding landscapes; gene promoters; G-quadruplex